Effect of environmental acidification on hepatic tissue A1AT kinetics of fish during acclimation - Shobharani, P; Bhaskar, M; Madhuri, E; Govindappa, S (Indian Journal of Fisheries, 2011)
Fresh water fish, Tilapia mossambica (Peters) were subjected to acclimation to sublethal acidic (pH 4.0) water and its impact on the hepatic tissue Alanine Amino Transferase (A1AT) activitiy was studied. The studies on substrate dependency of the enzyme showed significant increase in the activity levels of the enzyme in acclimated animals over the controls at all the substrate concentrations. The maximum per cent increase after acclimation was 25 p moles of substrate concentration. The pH dependency analysis recorded significant elevation in the activity level of the enzyme in acclimated tissues over the control at all the pH values studied. The temperaSHre dependency studies revealed maximum activity of the enzyme in control tissue at 30Â°C, whereas it was 40Â°C in experimental. It can be concluded that the process of acclimation to acidic environment induces adaptive mechanisms as a compensatory measure into enzymatic activities as evidenced by the activity of A1AT which in turn provides resistance to fish leading to successfull survival in extreme acidic waters